2020
DOI: 10.1002/ejic.202000032
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of ZnO/CNTs Nanocomposites via ALD for Photocatalysis Applications

Abstract: Vertically aligned carbon nanotubes (VA-CNTs) of 2.3 μm in height were produced by thermal chemical vapor deposition (TCVD) on Si/SiO 2 substrates. These carbon arrays were coated with zinc oxide (ZnO) via atomic layer deposition (ALD) technique. Conformal, uniform and very thin films (max. 26 nm) around the CNTs were obtained after 200 ALD cycles. The photocatalytic performance of these nanocomposite materials was tested in the degradation of rhodamine B, a harmful dye present in food and textile wastewaters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Additionally, these findings can be understood considering that the photocatalytic process is a photon assisted chemical reaction taking place at the material's surface, making it strongly affected by the exposed surface area, and the improved photocatalytic efficiency can be attributed to the synergistic effect between the metal oxides and carbon nanotubes, rather than its individual components. 20 In this context, the 200 ALD cycles were kept fixed while the deposition temperature was varied from 100 °C to 300 °C to evaluate the impact of the amorphous and crystalline nature of the TiO 2 films on the photocatalytic activity towards RhB degradation. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, these findings can be understood considering that the photocatalytic process is a photon assisted chemical reaction taking place at the material's surface, making it strongly affected by the exposed surface area, and the improved photocatalytic efficiency can be attributed to the synergistic effect between the metal oxides and carbon nanotubes, rather than its individual components. 20 In this context, the 200 ALD cycles were kept fixed while the deposition temperature was varied from 100 °C to 300 °C to evaluate the impact of the amorphous and crystalline nature of the TiO 2 films on the photocatalytic activity towards RhB degradation. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Oliveira et al fabricated ZnO ALD coatings on vertically aligned carbon nanotubes (CNTs). 115 Photogenerated electrons effectively migrated from the conduction band of ZnO to the CNTs, diminishing the recombination of charge carriers to some extent. Thus, the optimized 100-cycle ZnO ALD-coated CNT composites resulted in 77% RhB degradation after 7 h under UV irradiation, ca.…”
Section: Catalysis Determined By Substrate-enhanced Synergymentioning
confidence: 99%
“…The electrons become trapped in CNT structure and therefore do not spontaneously return to the valance band. Oliveira et al [7] revealed the better photocatalytic performance of ZnO/CNTs photocatalyst than the pristine ZnO probably due to a shift in the absorption light range. The photocatalytic activity can be further improved by combining rare-earth elements with ZnO/CNTs system.…”
Section: Introductionmentioning
confidence: 99%